The origin of malarial parasites in orangutans. - M Andreína Pacheco; Michael J C Reid; Michael A Schillaci; Carl A Lowenberger; Biruté M F Galdikas; Lisa Jones-Engel; Ananias A Escalante (PLoS ONE, 2012)
Recent findings of Plasmodium in African apes have changed our perspectives on the evolution of malarial parasites in hominids. However, phylogenetic analyses of primate malarias are still missing information from Southeast Asian apes. In this study, we report molecular data for a malaria parasite lineage found in orangutans.We screened twenty-four blood samples from Pongo pygmaeus (Kalimantan, Indonesia) for Plasmodium parasites by PCR. For all the malaria positive orangutan samples, parasite mitochondrial genomes (mtDNA) and two antigens: merozoite surface protein 1 42 kDa (MSP-1(42)) and circumsporozoite protein gene (CSP) were amplified, cloned, and sequenced. Fifteen orangutans tested positive and yielded 5 distinct mitochondrial haplotypes not previously found. The haplotypes detected exhibited low genetic divergence among them, indicating that they belong to one species. We report phylogenetic analyses using mitochondrial genomes, MSP-1(42) and CSP. We found that the orangutan malaria parasite lineage was part of a monophyletic group that includes all the known non-human primate malaria parasites found in Southeast Asia; specifically, it shares a recent common ancestor with P. inui (a macaque parasite) and P. hylobati (a gibbon parasite) suggesting that this lineage originated as a result of a host switch. The genetic diversity of MSP-1(42) in orangutans seems to be under negative selection. This result is similar to previous findings in non-human primate malarias closely related to P. vivax. As has been previously observed in the other Plasmodium species found in non-human primates, the CSP shows high polymorphism in the number of repeats. However, it has clearly distinctive motifs from those previously found in other malarial parasites.The evidence available from Asian apes indicates that these parasites originated independently from those found in Africa, likely as the result of host switches from other non-human primates.